T-bet: biological functions, molecular mechanisms, and therapeutic applications: a systematic review - Yang, Xiaowen; Sun, Min; Tang, Xinyi; Zhang, Xiaoyuan; Shen, Wenzhi (Frontiers in Immunology, 2026)
T-bet is a transcription factor predominantly expressed in immune cells, and it has been associated with a range of physiological and pathological processes, including the differentiation of various immune cell types, the development of immune-related diseases, and tumor progression. Despite notable advancements in the field, current research on T-bet remains fragmented, primarily concentrating on functional studies within specific cell types or the progression of particular diseases. This review aims to provide a comprehensive synthesis of the most recent findings regarding the role of T-bet in various diseases, with an emphasis on elucidating its molecular mechanisms and potential clinical applications. We underscore the involvement of T-bet in the pathogenesis of systemic diseases, including autoimmune disorders, infectious diseases, allergic conditions, endocrine disorders, psychiatric illnesses, and chromosomal abnormalities. Furthermore, we summarize its role in the development of various malignant tumors, such as esophageal cancer, gastric cancer, breast cancer, colon cancer, prostate cancer, and hematological malignancies. Additionally, we discuss the impact of T-bet on several critical processes in tumor biology, including tumor cell proliferation, apoptosis, epithelial-mesenchymal transition (EMT), metastasis, immune cell infiltration, and iron-induced apoptosis. We also assess the potential of T-bet as a prognostic and therapeutic target for tumors. In conclusion, T-bet may serve as a significant biomarker for the diagnosis and treatment of immune disorders and cancer, as well as a target for innovative immunotherapeutic strategies aimed at addressing tumors and immune-related diseases.